IDENTIFIKASI KALSIUM YANG TERLARUT DALAM FRAKSI ETIL ASETAT DAN AIR DARI DAUN DUDUK (DESMODIUM TRIQUETRUM (L) DC) SECARA IN VITRO DENGAN TEHNIK AKTIVASI NEUTRON CEPAT - Kamal, Zainul; Yazid, M.; Sapto Aji, Rani (Lembaga Penelitian Universitas YARSI, 2005)
The study on the solubility of calcium kidney stone in the ethyl acetate and water fraction of Duduk leaves was intended to investigate the efectiveness of the kidney stone solubility. The kidney stone was obtained after surgery, and analyzed applaying the infrared spectrophotometer to identify qualitatively the type of kidney stone. The study was performed by dissolving the calcium kidney stone 100 mg in 10 ml fraction of ethyl acetate and water Duduk leaves respectively. The mixtures were shaken and incubated at 370C for 4 hours in a waterbath and were then filtered. The solubility of calcium was determined by the rapid neutron activation tehnique. The result indicated that calcium solubilitty in the water fraction was better than that in the ethyl acetate fraction.